Produção e qualidade do leite em cabras 1/2 Boer-Saanen, em lactação, suplementadas com diferentes volumosos - Osmari, Elisa Köhler (2007)
The experiment was conducted to evaluate the supply of different roughages on the feed intake, yield milk, physicochemical composition and fatty acids profile of Boer-Saanen goats in a semi-intensive production system. Eigthteen primiparous were used in the trial, with parturition season beginning in the end of July util 19 days later, in August. The goats were distributed in three communal pens, according to the ad libitum supplement (SUP) imposed: sorghum silage treatment (SST), com silage treatment (CST) and mulberry hay treatment (MHT), with dry matter intake (DM1) controlled daily for each pen. Nineteen days after parturition, by using the daily milk production per animal, it was calculated the average daily production per week (ADPW), which was gathered in three periods (PER): 1 period (34-40 days postparturitionl7 days); II period (64-70 days post-parturitionl7 days) and ifi (125-13 1 days post-parturitionl7 days). Daily spot-average of each period (DSAP) was calculated and obtained by milk yield from reference date of ADPW periods, which later were correlated to monthly fat composition (F), protein (CP), lactose (LAC), total solids (TS) and somatic celis count (SCC). For acidity (ACID) and density (DENS), which were sampled weekly, data was regrouped in 37, (81±13)/2, 136 e (151±10)12 days postkidding. To lipid profile analysis, three milk samples were regrouped in two periods (PER): the first in August (winter) and the second comprising the mean values of November and December (spring-summer). With mixed modeis, the animal error was input as a random effect, two PER were taken for lipid profile analysis; three PER for the centesimal composition, ADPW and DSAP; and four PER for ACID and DENS, beyond three roughages as fixed effects. The greatest DM1 was observed for MHT, followed by CST and SST. CST presented greater acceptance among goats than SST. ADPW showed lower variation than DSAP. There was no difference among SUP for milk composition, only for PER. CP did not show any differences regarding SUP, but for PER x SUP (p<0.01). TS was lower in PER II of lactation due to decrease in F and LAC and increase in CP and ACID in PER III, with higher values of DENS in PER I and III because of the high SCC, which was increased in PER II due to mastitis. C8:O, C17:O, C17:ln-9, C18:O, C18:ln-9, C18:ln-7, C18:2n-6, transCl8:2n-6, C18:2n-6 and MUFA (monounsaturated fatty acids) had decreased at the end of lactation, while C4:O, (14:1, C15:0, C16:0, and the sum of saturated fatty acids (SFA) had increased, with a tendency of SUP favoring SST and MHT in C18: ln-9 (P<O.07) and MHT in C18:2n-6 (P<0.07). C14:0 suffered effect of SUP and PER, with the second period being greater and CST also greater than MHT, but not differing from SST. There was significant difference for acid SUP, PER and interaction for polyunsaturated fatty acids (PUFA), n6 and PUFAISFA. The effects of PER and interaction for C17:0 increased MHT and CST in August and MHT and SST in the second period. The conjugated acid linoleic increased in period two, and SUP x PER provided an increase of MHT and SST in period two. For C18:3n-3, SUP and SUP x PER was significant, favoring MHT in PER two, with higher mean values in August. Ali the supplements studied provided great n6/n3 ratio (4.34) and high CLÃ (0.92), but low n-3 (0.64) and PUFAISFA (0.05). MHT and beginning of lactation provided milk with better lipid profile.